Effect of didactic lectures on obesity documentation and counseling among internal medicine residents - Vicky Ren; Kathleen Ellison; Jonathan Miller; Kiran Busireddy; Erin Vickery; Mukta Panda; Rehan Qayyum (Greater Baltimore Medical Center, 2016)
Background: Screening adult patients for obesity and offering appropriate counseling and treatment for weight loss is recommended. However, many healthcare providers feel ill-equipped to address this topic. Objective: We examined whether didactic presentations lead to increased obesity documentation and counseling among internal medicine (IM) residents. Methods: We reviewed medical records of patients seen at the IM Resident Continuity Clinic during April 2015. Residents were provided feedback at two didactic presentations during May 2015. To examine the effect of this intervention, we repeated medical record review during June 2015. For both reviews, we abstracted patient-specific (i.e., age, body mass index [BMI], race, sex, and number of comorbid diagnoses) and resident-specific (i.e., sex and training level) data as well as evidence of obesity documentation and counseling. We used logistic regression models to examine the effect of intervention on obesity documentation and counseling, adjusting for patient- and resident-specific variables. Results: Of the 278 patients with BMI≥30 kg/m2, 139 were seen before and 139 after the intervention. Intervention had no effect on obesity documentation or counseling with or without adjustment for confounding variables (both P>0.05). In adjusted post-hoc analyses, each additional comorbidity increased the odds of obesity documentation by 8% (OR=1.08; 95% CI=1.05-1.11; P<0.001). In addition, as compared to postgraduate year (PGY) 1 residents, PGY-3 residents were 56% (OR=0.44; 95% CI=0.21-0.95; P=0.03) less likely to counsel obese patients. Conclusions: Obesity is inadequately addressed in primary care settings, and didactic presentations were unable to increase obesity documentation or weight loss counseling. Future research to identify effective interventions is needed.